2016
DOI: 10.1111/and.12564
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of arsenic on semen and hormonal profile and their amelioration with vitamin E in Teddy goat bucks

Abstract: The present environmental study has been planned to investigate the toxic effects of arsenic on reproductive functions of Teddy bucks as well as to examine whether these toxic effects are ameliorated by vitamin E. Sixteen adult Teddy bucks were divided randomly into four equal groups A, B, C and D with following treatment: A (control), B (sodium arsenite 5 mg kg BW day ), C (vit E 200 mg kg BW day + Arsenic 5 mg kg BW day ) and D (vit E 200 mg kg BW day ). This treatment was continued for 84 days. Semen qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
13
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 32 publications
7
13
1
Order By: Relevance
“…The results indicated an average semen volume 1.19 ± 0.03 ml. The results of our study are in well agreement with previous findings Zubair, Ahmad, Gul, and Ali () and Okere et al. ().…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The results indicated an average semen volume 1.19 ± 0.03 ml. The results of our study are in well agreement with previous findings Zubair, Ahmad, Gul, and Ali () and Okere et al. ().…”
Section: Resultssupporting
confidence: 94%
“…These findings were similar with Bitto and Egbunike () while Zubair et al. () reported the higher values. The morphological abnormal spermatozoa in the present study were 6.05% ± 0.29% which were similar with the Catunda et al.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, products manufactured from goat and sheep milk, such as yogurt, have be shown to contain metals such as arsenic [37]. In another context, arsenic has been shown to have a genotoxic and immunotoxic effect on goats [38], while effects have also been found on Luteinizing Hormone (LH) and Follicle Stimulating Hormone (FSH) concentrations and sperm quality in Teddy goats exposed to sodium arsenite [39]. In this sense, by means of the consumption of water with high concentrations of arsenic, environmental contamination is a significant problem for animal health and, consequently, for human health via its transmission up the food chain.…”
Section: Discussionmentioning
confidence: 99%
“…Animal and In-Vitro Studies; Sudha, (2012), reported that As caused the reduction in antioxidant enzymes by increasing oxidative stress, and this was corroborated by the damages of the sperm DNA and instability in nuclear constituents (Rajesh et al, 2002). The administration of 5 mg sodium arsenite/kg body weight for 12 weeks to Teddy buck goat caused a significant reduction in sperm count, motility, and male reproductive hormones (Zubair et al, 2016). Male rats exposed to sodium arsenite at 5 mg/L for 4 weeks in drinking water also resulted in decreased testicular weights, accessory sex organ weights, and epididymal sperm counts, as well as extensive degeneration of a wide variety of germ cells at stage VII of the spermatogenic cycle (Jana et al, 2006).…”
mentioning
confidence: 99%